Finding of bounded solutions to linear impulsive systems - Asrorov, Farkhod; Sobchuk, Valentyn; Kurylko, Оlexandr (Eastern-European Journal of Enterprise Technologies, 2019)
The problem of the existence of bounded on the entire real axis solutions to linear nonhomogeneous systems of differential equations undergoing impulsive perturbations at the fixed moments of time is investigated. Sufficient conditions for the hyperbolicity of solutions to the homogeneous multidimensional impulsive system are obtained. The derived conditions are applied to the study of the bounded solutions to the nonhomogeneous impulsive system. Sufficient conditions for the existence of a unique bounded solution to the nonhomogeneous system in the case of weak regularity of the corresponding homogeneous system are formulated. The advantage of such an approach is that the established conditions can be effectively tested for specific classes of impulse-perturbed systems, since they are formulated in terms of coefficients of initial problems. The obtained conditions allow applying classical solution methods of differential equations for the propositions on solvability and continuous dependence of solutions on parameters of the impulsive systems. The theory of systems with impulsive actions has wide possibilities for its application. Many evolution processes in physics, engineering, automatic control, biology, economics are exposed to short-term perturbations during their evolution. For example, processes with abrupt changes are observed in mechanics (spring movement under shock influence, functioning of the clock mechanism, change of rocket speed at separation stages), in radio engineering (generation of impulses of various forms). Similar processes are also observed in biology (heart beat, cell division), biotechnology (growing biocomposites), and control theory (industrial robots). Therefore, qualitative investigation of impulsive systems in this work is a relevant challenge of the modern theory of mathematical modeling